“It Permeates the Whole Fabric of Your Life”: The Experience of Scholars Who Have Studied Self-Directed Learning - Robert C. Donaghy (Adult Education Research Conference, 2006)
A recent dissertation presented a new and different view of self-directed learning. This research presents the stories of eight scholars who have studied this topic over the years. Implications for research and practice are discussed.
Keywords: Phenomenology; self-directed learning; and qualitative research